Implementation of Science Virtual Class Based Schoology to Improve Students’ Critical Thinking Skill - Budhiman, Arief; Ellianawati, Ellianawati; Wahyuni, Siti (Journal of Innovative Science Education, 2021)
Implementing appropriate strategies in learning so that students acquire 21st century skills is an important thing for teachers to do. These skills will equip students to adapt to the needs of their era. One of the skills is critical thinking. However, during the Covid-19 pandemic, all educational institutions were encouraged to carry out online learning to prevent massive transmission of the corona virus. In science learning, it emphasizes students to learn independently by providing clear instructions from the teachers to practice critical thinking. One of the media that can bridge the needs of students to learn independently in practicing critical thinking is Schoology. The purpose of this research was to find out the influence of schoology virtual science-based learning in improving critical thinking of students. The study was a quasi-experimental design. The sample of this research were 64 students taken through purposive sampling. The improvement of students' critical thinking skills was identified from the essay test given. The results showed that the size impact (d) reached high category (1.85). It means that the schoology virtual science-based learning have a high influence in improving students' critical thinking skill. Furthermore, the t-test showed a sig value. 0.000 and N-Gain in the experimental class reached 0.50 while the control class reached 0.27. It indicates that the implementation of schoology virtual science-based learning can improve students' critical thinking skill.